Optimizing lipopeptide bioactivity: The impact of non-ionic surfactant dressing - Ágnes Ábrahám; Gergő Gyulai; Judith Mihály; Andrea Horváth; Orsolya Dobay; Zoltán Varga; Éva Kiss; Kata Horváti (Journal of Pharmaceutical Analysis)
The aim of the research is to increase the applicability of lipopeptides as drugs. To this end, non-ionic triblock copolymers, namely poloxamers, were applied. The physico-chemical properties of poloxamers vary depending on the length of the blocks. In our study, we experimented with different types and systematically investigated the variation of the critical micelle concentration (CMC) of poloxamers at 25 and 37 °C in different media. In addition, the cytotoxicity of the different poloxamer micelles on three different cell lines was evaluated, and based on the results, Plur104, Plur123, and Plur127 were selected. Fatty acid elongated derivatives of a short antibacterial peptide (pL1), a medium-sized anticancer peptide (pCM15), and a branched-chain vaccine antigen (pATIPC) were used as lipopeptide models, and their formulations with the selected poloxamers were investigated. The solubility and homogeneity of the lipopeptides were significantly increased, and dynamic light scattering (DLS) measurements showed the formation of small particles of around 20 nm, which were well reproducible and storable. Similar homogenous micelle formation was observed after freeze-drying and reconstitution with water. The pL1 lipopeptide, formulated with the selected poloxamers, exhibited enhanced antibacterial activity with significantly reduced haemolytic side effects. The pCM15 peptide, when incorporated into poloxamer micelles, showed significantly enhanced cytotoxicity against tumor cells. Additionally, the internalization rate of poloxamer-formulated pATIPC peptide by antigen-presenting model cells exceeded that of the unformulated peptide. Our results demonstrate the potential of poloxamers as promising tools for the formulation of lipopeptides and for the optimization of their selectivity.